2023
DOI: 10.1038/s41598-023-34327-0
|View full text |Cite
|
Sign up to set email alerts
|

Training a quantum measurement device to discriminate unknown non-orthogonal quantum states

Abstract: Here, we study the problem of decoding information transmitted through unknown quantum states. We assume that Alice encodes an alphabet into a set of orthogonal quantum states, which are then transmitted to Bob. However, the quantum channel that mediates the transmission maps the orthogonal states into non-orthogonal states, possibly mixed. If an accurate model of the channel is unavailable, then the states received by Bob are unknown. In order to decode the transmitted information we propose to train a measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Thus, hybrid optimization algorithms are used whenever the objective function can be evaluated more efficiently on a quantum computer than on a classical one. This is the case for applications to quantum chemistry [6][7][8], quantum control [9][10][11], quantum simulation [12,13], entanglement detection [14][15][16], state estimation [17][18][19][20][21], quantum machine learning [22][23][24][25][26], error correction [27], graph theory [28][29][30], differential equations [31][32][33], and finances [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, hybrid optimization algorithms are used whenever the objective function can be evaluated more efficiently on a quantum computer than on a classical one. This is the case for applications to quantum chemistry [6][7][8], quantum control [9][10][11], quantum simulation [12,13], entanglement detection [14][15][16], state estimation [17][18][19][20][21], quantum machine learning [22][23][24][25][26], error correction [27], graph theory [28][29][30], differential equations [31][32][33], and finances [34].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that CSPSA can deliver better results in the estimation of pure states [19] and is robust against noise [21]. It has been applied to entanglement estimation [16], quantum state discrimination [26], and violation of the Clauser-Horne-Shimony-Holt inequality [94].…”
Section: Introductionmentioning
confidence: 99%